Compound containing boron and nitrogen, organic electroluminescent device and display device

By designing a boron nitrogen-containing compound as the luminescent layer material for organic electroluminescent devices, the problems of high driving voltage and low current efficiency in the prior art are solved, and lower driving voltage and higher current efficiency are achieved.

CN120118113APending Publication Date: 2025-06-10FUYANG SINEVA MATERIAL TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510235805.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-28
Publication Date
2025-06-10

AI Technical Summary

Technical Problem

In actual applications, existing organic electroluminescent devices have problems such as high driving voltage and low current efficiency, which affects their industrialization and application effects.

Method used

A boron nitrogen-containing compound is designed to be used as a light emitting layer material for organic electroluminescent devices to improve its luminescence performance.

Benefits of technology

By using boron nitrogen-containing compounds, the driving voltage of organic electroluminescent devices is effectively reduced, its current efficiency is improved, and its service life is extended.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005292707200000021
    Figure BDA0005292707200000021
  • Figure BDA0005292707200000022
    Figure BDA0005292707200000022
  • Figure BDA0005292707200000031
    Figure BDA0005292707200000031
Patent Text Reader

Abstract

The invention provides a compound containing boron and nitrogen, an organic electroluminescent device and a display device, and relates to the technical field of organic photoelectric display. By designing the structure of the compound containing boron and nitrogen, the obtained compound containing boron and nitrogen has excellent performance, and the organic electroluminescent device prepared by using the compound containing boron and nitrogen as a luminescent layer material has relatively low driving voltage and relatively high current efficiency.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of organic optoelectronic display, and particularly relates to a boron-nitrogen-containing compound, an organic electroluminescent device, and a display device. Background Art

[0002] An organic light emitting element (organic light emitting diode; OLED) is a display component that utilizes the phenomenon of self-luminescence. It has a large viewing angle. Compared with liquid crystal display components, OLED components are thinner, lighter, have a faster response speed, and can achieve flexible display. Therefore, its application as a full-color display component or a lighting device is highly anticipated.

[0003] Generally, the organic light emitting phenomenon refers to the phenomenon of converting electrical energy into light energy by using organic substances. An organic light emitting element utilizing the organic light emitting phenomenon usually has a structure including an anode, a cathode, and an organic layer sandwiched between the anode and the cathode.

[0004] Among them, in order to improve the efficiency and stability of the organic light emitting element, the organic layer is mostly composed of a multi-layer structure formed by different substances respectively. For example, it can be composed of a hole injection layer, a hole transport layer, a light emitting layer, an electron transport layer, an electron injection layer, etc. If a voltage is applied between the two electrodes in the structure of such an organic light emitting element, holes in the anode will be injected into the organic layer, and electrons in the cathode will also be injected into the organic layer. When the injected holes and electrons meet, excitons are formed. When the excitons release energy and transition to the ground state, photons will be emitted, thus generating light. Such an organic light emitting element is widely considered to have characteristics such as self-luminescence, high brightness, high efficiency, low driving voltage, wide viewing angle, high contrast, and high speed responsiveness.

[0005] Currently, the research on organic electroluminescent materials has been widely carried out in the academic and industrial fields. Among them, the light emitting layer material is an important part of the organic electroluminescent device. The transport performance and light emitting efficiency of the light emitting layer material restrict the industrialization of the light emitting device. Therefore, designing and searching for compounds that can be used as new OLED materials to overcome the deficiencies that occur in the actual application process is the focus and future research and development trend in the research work of OLED materials. Summary of the Invention

[0006] Aiming at the deficiencies of the prior art, the purpose of the present invention is to provide a boron-nitrogen-containing compound, an organic electroluminescent device, and a display device. Through the design of the structure of the boron-nitrogen-containing compound, the obtained boron-nitrogen-containing compound has excellent properties and is suitable for use as a light emitting layer material in an organic electroluminescent device.

[0007] To achieve this purpose, the present invention adopts the following technical solutions:

[0008] In a first aspect, the present invention provides a boron and nitrogen-containing compound having a structure shown in Formula I:

[0009]

[0010] In Formula I, R 1 , R 2 , R 3 , R 4 , R 5 are each independently selected from hydrogen, deuterium, substituted or unsubstituted C 1 -C 12 alkyl, substituted or unsubstituted C 6 -C 30 aryl, substituted or unsubstituted C 3 -C 30 heteroaryl, R 1 , R 2 , R 3 , R 4 , R 5 are the same or different; and at least one of R 1 , R 2 , R 3 , R 4 , R 5 has a structure shown in Formula II:

[0011]

[0012] The * in Formula II represents the connection site;

[0013] The substituents of the substitution are selected from deuterium, F, cyano, C 1 -C 12 alkyl, C 6 -C 30 aryl or C 3 -C 30 heteroaryl;

[0014] The hydrogen atoms in Formula I and Formula II can each independently be substituted by deuterium, F, cyano, C 1 -C 12 alkyl, C 6 -C 30 aryl or C 3 -C 30 heteroaryl.

[0015] Preferably, the C 1 -C 12 alkyl is selected from methyl, ethyl, propyl, isopropyl, butyl, tert-butyl, pentyl, pivalyl, n-hexyl or cyclohexyl.

[0016] More preferably, the C1 ~C 12 The alkyl group is selected from methyl, ethyl, isopropyl or tert-butyl.

[0017] In the present invention, the aryl group refers to the general term of the monovalent group remaining after removing one hydrogen atom from the aryl nuclear carbon of the aromatic hydrocarbon molecule; the aryl group includes a monocyclic aryl group or a polycyclic aryl group.

[0018] Preferably, the C 6 ~C 30 The aryl group is selected from phenyl, biphenyl, terphenyl, naphthyl, anthryl, indenyl, fluorenyl, perylenyl, phenanthryl, pyrenyl, fluoranthenyl, fluorenyl, spirobifluorenyl or benzophenanthryl.

[0019] More preferably, the C 6 ~C 30 The aryl group is selected from phenyl, biphenyl or naphthyl.

[0020] In the present invention, the heteroaryl group refers to the general term of the group obtained by replacing one or more aryl nuclear carbons in the aryl group with heteroatoms; the heteroaryl group includes a monocyclic heteroaryl group or a polycyclic heteroaryl group.

[0021] Preferably, the heteroatom in the C 3 ~C 30 heteroaryl group is selected from oxygen, sulfur, nitrogen or silicon.

[0022] Preferably, the C 3 ~C 30 The heteroaryl group is selected from pyridyl, benzofuranyl, benzothiophenyl, dibenzofuranyl, dibenzothiophenyl, carbazolyl, diarylamino, benzofurancarbazolyl, benzofuranothiophenyl or triazinyl. More preferably, the C 3 ~C 30 The heteroaryl group is selected from pyridyl, dibenzofuranyl, dibenzothiophenyl or carbazolyl. Preferably, the boron and nitrogen-containing compound is selected from any one of Compounds 1 to 48:

[0023]

[0024]

[0025] Some specific structural forms of the boron and nitrogen-containing compound are listed in the present invention, but the boron and nitrogen-containing compound described in the present invention is not limited to these chemical structures listed. Any structure based on the structure shown in Formula I, where R 1 , R 2 , R 3 , R 4 , R 5 meeting the above-defined conditions should be included.

[0026] Second aspect, the present invention provides an organic electroluminescent device, and the organic electroluminescent device includes a boron-nitrogen-containing compound as described in the first aspect.

[0027] Preferably, the organic electroluminescent device includes a first electrode, a second electrode, and an organic layer disposed between the first electrode and the second electrode.

[0028] The material of the organic layer includes a boron-nitrogen-containing compound as described in the first aspect.

[0029] Preferably, the organic layer includes a light-emitting layer.

[0030] The light-emitting layer includes a boron-nitrogen-containing compound as described in the first aspect.

[0031] Furthermore, the light-emitting layer is prepared by a vapor deposition method.

[0032] Preferably, the light-emitting layer includes a host material and a doping material;

[0033] The doping material includes a boron-nitrogen-containing compound as described in the first aspect.

[0034] Third aspect, the present invention provides a display device, and the display device includes an organic electroluminescent device as described in the second aspect.

[0035] Compared with the prior art, the present invention has the following beneficial effects:

[0036] By designing the structure of the boron-nitrogen-containing compound, the obtained boron-nitrogen-containing compound has good light-emitting performance and can be used to prepare an organic electroluminescent device. Especially as the light-emitting layer material in the organic electroluminescent device, it can effectively reduce the driving voltage of the organic electroluminescent device and improve the current efficiency of the organic electroluminescent device. Specific Embodiments

[0037] To facilitate the understanding of the present invention, preparation examples and embodiments are listed as follows. Those skilled in the art should understand that the preparation examples and embodiments are only for helping to understand the present invention and should not be regarded as specific limitations on the present invention.

[0038] Synthesis Example 1

[0039] This example provides a synthesis method of Compound 1, and the synthesis method is as follows:

[0040]

[0041] (1) Synthesis of Intermediate 1-1

[0042] Under nitrogen protection, 400 ml of tetrahydrofuran and 0.1 mol of 5-chloro-5-phenyl-9H-9-silafluorene were added to the reaction bottle. After being fully dissolved, the temperature was lowered to -78°C. Then, a 1.7 M tert-butyl lithium pentane solution (containing 0.1 mol of tert-butyl lithium) was added dropwise at -78°C. After the addition was completed, the temperature was kept at -78°C for 0.5 h. Then, 100 ml of 3,5-dibromo-4-chloroiodobenzene tetrahydrofuran solution (containing 0.1 mol of 3,5-dibromo-4-chloroiodobenzene) was added dropwise at -78°C. After the addition was completed, the temperature was naturally raised to room temperature. The mixture was poured into 2000 ml of water and stirred for 1 h. The crude solid was filtered with a suction funnel and the crude solid was recrystallized with a mixed solvent of toluene and ethanol to obtain intermediate 1-1.

[0043] The mass spectrometry of intermediate 1-1 revealed a mass-to-charge ratio (m / z) of 523.9.

[0044] (2) Synthesis of intermediate 1-2

[0045] Under nitrogen protection, add 200 mL of dry toluene, 0.1 mol of intermediate 1-1, 0.1 mol of amine-1, and 0.001 mol of Pd(dba) into a 500 mL three-necked flask. 2 (bis(dibenzylideneacetone palladium), 4g of a 10% tri-tert-butylphosphine toluene solution (containing 0.002mol tri-tert-butylphosphine) and 0.3mol sodium tert-butoxide, heated to reflux for 12h, cooled to room temperature, added water to separate, then the organic layer was washed with water until neutral, dried with magnesium sulfate, filtered to remove magnesium sulfate, concentrated to dryness, and crystallized with ethanol to obtain intermediate 1-2;

[0046] The obtained intermediate 1-2 was subjected to mass spectrometry detection, and the mass-to-charge ratio (m / z) was measured to be 669.0.

[0047] (3) Synthesis of intermediate 1-3

[0048] Under nitrogen protection, add 200 mL of dry toluene, 0.1 mol of intermediate 1-2, 0.1 mol of diphenylamine, and 0.001 mol of Pd(dba) into a 500 mL three-necked flask. 2 (bis(dibenzylideneacetone palladium), 4g of a 10% tri-tert-butylphosphine toluene solution (containing 0.002mol tri-tert-butylphosphine) and 0.3mol sodium tert-butoxide, heated to reflux for 12h, cooled to room temperature, added water to separate, then the organic layer was washed with water until neutral, dried with magnesium sulfate, filtered to remove magnesium sulfate, concentrated to dryness, and crystallized with ethanol to obtain intermediate 1-3;

[0049] The obtained intermediate 1-3 was subjected to mass spectrometry detection, and the mass-to-charge ratio (m / z) was measured to be 758.2.

[0050] (4) Synthesis of Compound 1

[0051] Under nitrogen protection, the reaction bottle containing 0.01 mol of intermediate 1-3 and 100 ml of toluene was cooled to 0°C, and then a pentane solution of 1.7 M tert-butyl lithium (containing 0.3 mol tert-butyl lithium) was added dropwise to the reaction system. After the addition was completed, the temperature was raised to 70°C and stirred for 3 hours. Then the system was cooled to -40°C, 0.012 mol of boron tribromide was added dropwise, and after the addition was completed, the temperature was raised to 25°C and stirred for 4 hours. After the reaction was completed, saturated Na 2 S 2 O 3 Aqueous solution and saturated NaHCO 3 The organic layer was washed with water until it was neutral, dried with magnesium sulfate, filtered to remove the magnesium sulfate, concentrated to dryness, separated by silica gel column chromatography, and eluted with a mixed solvent of petroleum ether and dichloromethane (the volume ratio of petroleum ether to dichloromethane was 5:1) to obtain compound 1.

[0052] The obtained compound 1 was subjected to mass spectrometry detection, and the mass-to-charge ratio (m / z) was measured to be 732.2.

[0053] Synthesis Example 2

[0054] This embodiment provides a synthesis method of compound 2, and the synthesis method is as follows:

[0055]

[0056] (1) Synthesis of intermediate 2-1

[0057] Under nitrogen protection, add 200 mL of dry toluene, 0.1 mol of bromide-1, 0.1 mol of aniline, and 0.001 mol of Pd(dba) into a 500 mL three-necked flask. 2 (bis(dibenzylideneacetone palladium), 4g of a 10% tri-tert-butylphosphine toluene solution (containing 0.002mol tri-tert-butylphosphine) and 0.3mol sodium tert-butoxide, heated to reflux for 12h, cooled to room temperature, added water to separate, then the organic layer was washed with water until neutral, dried with magnesium sulfate, filtered to remove magnesium sulfate, concentrated to dryness, and crystallized with ethanol to obtain intermediate 2-1;

[0058] The mass spectrometry of intermediate 2-1 revealed a mass-to-charge ratio (M / Z) of 425.2.

[0059] (2) Synthesis of intermediate 2-2

[0060] Under nitrogen protection, add 200 mL of dry toluene, 0.1 mol of 2,6-dibromochlorobenzene, 0.1 mol of intermediate 2-1, and 0.001 mol of Pd(dba) into a 500 mL three-necked flask. 2 (bis(dibenzylideneacetone palladium), 4g of a 10% tri-tert-butylphosphine toluene solution (containing 0.002mol tri-tert-butylphosphine) and 0.3mol sodium tert-butoxide, heated to reflux for 12h, cooled to room temperature, added water to separate, then the organic layer was washed with water until neutral, dried with magnesium sulfate, filtered to remove magnesium sulfate, concentrated to dryness, and crystallized with ethanol to obtain intermediate 2-2;

[0061] The mass spectrometry of intermediate 2-2 revealed a mass-to-charge ratio (M / Z) of 613.1.

[0062] (3) Synthesis of intermediate 2-3

[0063] Under nitrogen protection, add 200 mL of dry toluene, 0.1 mol of amine-1, 0.1 mol of intermediate 2-2, and 0.001 mol of Pd(dba) into a 500 mL three-necked flask. 2 (bis(dibenzylideneacetone palladium), 4g of a 10% tri-tert-butylphosphine toluene solution (containing 0.002mol tri-tert-butylphosphine) and 0.3mol sodium tert-butoxide, heated to reflux reaction for 12h, cooled to room temperature, added water to separate, then the organic layer was washed with water until neutral, dried with magnesium sulfate, filtered to remove magnesium sulfate, concentrated to dryness, and crystallized with ethanol to obtain intermediate 2-3;

[0064] The mass spectrometry of intermediate 2-3 revealed a mass-to-charge ratio (M / Z) of 758.2.

[0065] (4) Synthesis of Compound 2

[0066] Under nitrogen protection, the reaction bottle containing 0.01 mol of intermediate 2-3 and 100 ml of toluene was cooled to 0°C, and then a pentane solution of 1.7 M tert-butyl lithium (containing 0.3 mol tert-butyl lithium) was added dropwise to the reaction system. After the addition was completed, the temperature was raised to 70°C and stirred for 3 hours, and then the system was cooled to -40°C and 0.012 mol of boron tribromide was added dropwise. After the addition was completed, the temperature was raised to 25°C and stirred for 4 hours. After the reaction was completed, saturated Na 2 S 2 O 3 Aqueous solution and saturated NaHCO 3 The organic layer was washed with water until neutral, dried with magnesium sulfate, filtered to remove the magnesium sulfate, concentrated to dryness, separated by silica gel column chromatography, and eluted with a mixed solvent of petroleum ether and dichloromethane (the volume ratio of petroleum ether to dichloromethane was 5:1) to obtain compound 2.

[0067] The obtained compound 2 was subjected to mass spectrometry, and the measured mass-to-charge ratio (m / z) was 732.2.

[0068] Synthesis Example 3

[0069] This example provides a method for synthesizing compound 17, and the synthesis method is as follows:

[0070]

[0071] Referring to the synthesis method of Synthesis Example 1, amine-2 benzene with an equimolar amount was used to replace amine-1 in Synthesis Example 1, and bis(4-tert-butylphenyl)amine with an equimolar amount was used to replace diphenylamine in Synthesis Example 1. Under other unchanged conditions, compound 17 can be obtained.

[0072] Compound 17 was subjected to mass spectrometry: the measured charge-to-mass ratio (m / z): 900.4.

[0073] Synthesis Example 4

[0074] This example provides a method for synthesizing compound 21, and the synthesis method is as follows:

[0075]

[0076] Referring to the synthesis method of Synthesis Example 3, amine-3 with an equimolar amount was used to replace amine-2 in Synthesis Example 3. Under other unchanged conditions, compound 21 can be obtained.

[0077] Compound 21 was subjected to mass spectrometry, and the measured charge-to-mass ratio (m / z): 956.5.

[0078] Synthesis Example 5

[0079] This synthesis example provides a method for synthesizing compound 28, and the synthesis method is as follows:

[0080]

[0081] 0.01 mol of compound 1 was added to a reaction flask, then 160 ml of deuterated benzene and 0.05 mol of trifluoromethanesulfonic anhydride were added. Under nitrogen protection, the temperature was raised to 80 °C, and the reaction was maintained for 24 h. After cooling to room temperature, the reaction was quenched with saturated aqueous sodium bicarbonate solution, washed with water until neutral, dried over anhydrous magnesium sulfate, and then passed through a silica gel column. The obtained crude product was recrystallized with a mixed solvent of toluene and ethanol to obtain compound 28.

[0082] The obtained compound 28 was subjected to mass spectrometry: the measured mass-to-charge ratio (m / z) was 776.4.

[0083] Referring to the synthesis methods of the above compounds and combining with common organic synthesis means, compounds 29, 31, 34, 36, and 47 were prepared and subjected to mass spectrometry detection. The test results are shown in Table 1 below.

[0084] Table 1

[0085]

[0086]

[0087] For compounds without specific synthesis steps listed, they can be prepared by combining the common general knowledge in the art with the above examples.

[0088] The specific structures of some compounds used in the following device examples and device comparative examples are as follows:

[0089]

[0090] In the following device example, the boron-nitrogen-containing compound provided by the present invention is selected as the luminescent layer doping material in the organic electroluminescent device, and in the device comparative example, the above BD-1, BD-2, and BD-3 are selected as the luminescent layer doping materials in the organic electroluminescent device.

[0091] Device Example 1

[0092] This device example provides an organic electroluminescent device, using compound 1 provided by the synthesis example 1 of the present invention as the luminescent layer doping material; and in this example, the luminescent layer is prepared by evaporation.

[0093] The structure of the organic electroluminescent device is as follows:

[0094] ITO / HT(40nm) / BH: Compound 13% / TPBI(30nm) / LiF(0.5nm) / Al(150nm).

[0095] The preparation method of the above organic electroluminescent device is as follows:

[0096] The glass substrate coated with the ITO transparent conductive layer (as the anode) is ultrasonically treated in a cleaning agent, then rinsed in deionized water, ultrasonically degreased in a mixed solvent of acetone and ethanol, then baked in a clean environment until completely dehydrated, cleaned with ultraviolet light and ozone, and bombarded with a low-energy cation beam on the surface to improve the surface properties and enhance the bonding ability with the hole injection layer;

[0097] The above glass substrate is placed in a vacuum chamber, evacuated to 1×10 -5 ~9×10 -3Pa, HT was vacuum-evaporated onto the anode as a hole transport layer at a deposition rate of 0.1 nm / s, and the deposited film thickness was 40 nm;

[0098] The light-emitting layer was vacuum-evaporated onto the hole transport layer at a deposition rate of 0.1 nm / s, and the deposited film thickness was 30 nm. The host material of the light-emitting layer was BH, and the doping material was Compound 1 provided by the present invention. 3% refers to the doping ratio of the doping material, that is, the volume ratio of the host material to the doping material in the light-emitting layer is 97:3.

[0099] The glass substrate on which the light-emitting layer had been deposited in the previous step was transferred to a vacuum chamber, and TPBI was vacuum-evaporated onto the light-emitting layer as the electron transport layer of the device at a deposition rate of 0.1 nm / s, and the deposited film thickness was 30 nm;

[0100] 0.5 nm of LiF and 150 nm of Al were vacuum-evaporated onto the electron transport layer as the electron injection layer and the cathode.

[0101] The brightness, driving voltage, and current efficiency of the fabricated organic light-emitting device were measured.

[0102] Device Examples 2-10

[0103] Device Examples 2-10 each provide an organic light-emitting device, which is different from Device Example 1 only in that the doping material of the light-emitting layer is different (see Table 2 for details), and other conditions are the same as those in Device Example 1.

[0104] Device Comparative Examples 1-3

[0105] Device Comparative Examples 1-3 each provide an organic light-emitting device, which is different from Device Example 1 only in that the doping material of the light-emitting layer is different (see Table 2 for details), and other conditions are the same as those in Device Example 1.

[0106] Performance Test

[0107] The driving voltage, current efficiency, and lifetime LT90 of the above-provided OLED devices were tested; among them, LT90 refers to the time required for the brightness to drop to 90% of the original brightness while keeping the current density unchanged when the initial brightness is 1000 nit. The test items include the brightness, driving voltage, and current efficiency of the organic light-emitting device. The data of the driving voltage, current efficiency, and LT90 are all relative values at a brightness of 1000 cd / m 2 (based on the test data of BD-1). The performance test results of the organic light-emitting device are shown in Table 2 below.

[0108] Table 2

[0109] Doping material <![CDATA[Required luminance / (cd / m 2 )]]> Driving voltage Current efficiency LT90 life Device comparative example 1 BD-1 1000 1 1 1 Device comparative example 2 BD-2 1000 1.24 1.04 0.93 Device comparative example 3 BD-3 1000 1.07 0.82 0.89 Device example 1 Compound 1 1000 0.76 1.11 1.32 Device example 2 Compound 2 1000 0.58 1.23 1.39 Device example 3 Compound 17 1000 0.71 1.23 1.36 Device example 4 Compound 21 1000 0.77 1.67 1.38 Device example 5 Compound 28 1000 0.75 1.12 1.82 Device example 6 Compound 29 1000 0.77 1.25 1.85 Device example 7 Compound 31 1000 0.74 1.31 1.25 Device example 8 Compound 34 1000 0.75 1.29 2.39 Device example 9 Compound 36 1000 0.65 1.21 1.55 Device example 10 Compound 47 1000 0.73 1.46 1.44

[0110] As can be seen from the above, through structural design, the present invention obtains a compound suitable as a doping material for the light-emitting layer, and the organic electroluminescent device prepared therefrom has a lower driving voltage, a higher current efficiency, and a longer service life.

[0111] The present invention uses the above embodiments to illustrate the detailed process flow of the present invention. However, the present invention is not limited to the above detailed process flow, that is, it does not mean that the present invention must rely on the above detailed process flow to be implemented. Those skilled in the art should understand that any improvement to the present invention, the equivalent substitution of each raw material of the product of the present invention, the addition of auxiliary components, the selection of specific methods, etc. all fall within the protection scope and the disclosure scope of the present invention.

Claims

1. A boron-nitrogen-containing compound, characterized in that The boron-nitrogen-containing compound has a structure as shown in Formula I: In Formula I, R1, R2, R3, R4, and R5 are each independently selected from hydrogen, deuterium, substituted or unsubstituted C1 to C 12 Alkyl, substituted or unsubstituted C6~C 30 Aryl, substituted or unsubstituted C3~C 30 Heteroaryl, R1, R2, R3, R4, R5 are the same or different; and at least one of R1, R2, R3, R4, R5 is a structure shown in Formula II: The substituted substituent is selected from deuterium, F, cyano, C1-C 12 Alkyl, C6~C 30 Aryl or C3~C 30 heteroaryl; * in Formula II represents the attachment site; The hydrogen atoms in formula I and formula II can be independently replaced by deuterium, F, cyano, C1-C 12 Alkyl, C6~C 30 Aryl or C3~C 30 Heteroaryl substitution.

2. The boron-nitrogen-containing compound according to claim 1, characterized in that C1~C 12 The alkyl group is selected from methyl, ethyl, propyl, isopropyl, butyl, tert-butyl, pentyl, tert-pentyl, n-hexyl or cyclohexyl.

3. The boron-nitrogen-containing compound according to claim 1, characterized in that C6~C 30 Aryl is selected from phenyl, biphenyl, terphenyl, naphthyl, anthracenyl, indenyl, fluorenyl, perylenyl, phenanthrenyl, pyrenyl, fluoranthenyl, spirobifluorenyl or triphenylenyl.

4. The boron-nitrogen-containing compound according to claim 1, characterized in that C3~C 30 The heteroatoms in the heteroaryl group are selected from oxygen, sulfur, nitrogen or silicon.

5. The boron-nitrogen-containing compound according to claim 1, characterized in that C3~C 30 The heteroaryl group is selected from benzofuranyl, benzothiophenyl, dibenzofuranyl, dibenzothiophenyl, carbazolyl, diarylideneamine, benzofuranocarbazolyl, benzofuranothiophenyl or triazine.

6. The boron-nitrogen-containing compound according to claim 1, characterized in that The boron-nitrogen-containing compound is selected from any one of compounds 1 to 48:

7. An organic electroluminescent device, characterized in that: The organic electroluminescent device comprises the boron-nitrogen-containing compound according to any one of claims 1 to 6.

8. The organic electroluminescent device according to claim 7, characterized in that: The organic electroluminescent device comprises a first electrode, a second electrode and an organic layer arranged between the first electrode and the second electrode; the organic layer comprises a light-emitting layer; and the light-emitting layer comprises the boron-nitrogen-containing compound.

9. The organic electroluminescent device according to claim 8, characterized in that: The light-emitting layer includes a main material and a doping material, and the doping material includes the boron-nitrogen-containing compound.

10. A display device, characterized in that: The display device comprises the organic electroluminescent device according to any one of claims 7 to 9.